2001
DOI: 10.1128/aem.67.10.4765-4772.2001
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Induced Inhibition of Growth of Desulfovibrio desulfuricans G20: Assessment of Its Toxicity and Correlation with Those of Zinc and Lead

Abstract: The toxicity of copper [Cu(II)] to sulfate-reducing bacteria (SRB) was studied by using Desulfovibrio desulfuricans G20 in a medium (MTM) developed specifically to test metal toxicity to SRB (R. K. Sani, G.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
4
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 186 publications
(120 citation statements)
references
References 55 publications
5
107
4
4
Order By: Relevance
“…This observation suggests a remarkable potential for application of these fungi in chromium biotreatment. Sani et al [62] had reported similar observation with Desulfovibrio desulfuricans where toxic concentration of the heavy metal ions, Cu(II), Pb(II) and Zn(II) utterly inhibited growth, but did not kill the cells of the organism. Although Ezzouhri et al [63] reported 10 -15 mM of Cr(VI) as the Minimum Inhibitory Concentration (MIC) for Aspergillus species, the results obtained however revealed that the response of the isolates to heavy metals depended on the metal tested, its concentration in the medium and on the isolate considered.…”
Section: Regeneration Of Fungal Cells After Initial Exposure To Cr(vi)supporting
confidence: 48%
See 1 more Smart Citation
“…This observation suggests a remarkable potential for application of these fungi in chromium biotreatment. Sani et al [62] had reported similar observation with Desulfovibrio desulfuricans where toxic concentration of the heavy metal ions, Cu(II), Pb(II) and Zn(II) utterly inhibited growth, but did not kill the cells of the organism. Although Ezzouhri et al [63] reported 10 -15 mM of Cr(VI) as the Minimum Inhibitory Concentration (MIC) for Aspergillus species, the results obtained however revealed that the response of the isolates to heavy metals depended on the metal tested, its concentration in the medium and on the isolate considered.…”
Section: Regeneration Of Fungal Cells After Initial Exposure To Cr(vi)supporting
confidence: 48%
“…Hexavalent chromium is highly toxic to a lot of microorganisms, and like other heavy metal ions such as Cu(II), Pb(II), Zn(II), etc. it may cause structural damage in cells and consequently a permanent effect on cell growth [34,62].…”
Section: Regeneration Of Fungal Cells After Initial Exposure To Cr(vi)mentioning
confidence: 99%
“…For the conditions of copper sulfate doses <0.5 mg·L −1 , the mortality rate constants were all less than 10 −3 h −1 , suggesting that the effect on the studied bacterium is negligible. Sani et al (2001) [63] reported an IC50 of 13.3 µM copper (3.3 mg copper sulfate pentahydrate·L −1 ) to sulfate-reducing bacteria (SRB) Desulfovibrio desulfuricans G20. When a higher dose was applied, 30 µM copper (7.4 mg copper sulfate pentahydrate·L −1 ), 100% of the SRB were killed in 25 h and no bacteria were detected after 384 h of incubation.…”
Section: Resultsmentioning
confidence: 99%
“…44) Bacterial growth was estimated by measurement of total cellular protein using the Bradford method. 11,[45][46][47] Cell viability also served as a visual check for contamination.…”
Section: Discussionmentioning
confidence: 99%